Antenatal predictors of incident and persistent postnatal depressive symptoms in rural Ethiopia: a population-based prospective study - Tesera Bitew; Charlotte Hanlon; Girmay Medhin; Abebaw Fekadu (BMC, 2019)
Abstract Background There have been few studies to examine antenatal predictors of incident postnatal depression, particularly in low- and middle-income countries (LMICs). The aim of this study was to investigate antenatal predictors of incident and persistent maternal depression in a rural Ethiopian community in order to inform development of antenatal interventions. Method A population-based prospective study was conducted in Sodo district, south central Ethiopia. A locally validated version of the Patient Health Questionnaire (PHQ-9) was used to assess antenatal (second and third trimesters) and postnatal (4-12 weeks after childbirth) depressive symptoms, with a PHQ-9 cut-off of five or more indicating high depressive symptoms. Poisson regression with robust standard errors was used to identify independent predictors of persistence and incidence of postnatal depressive symptoms from a range of antenatal, clinical and psychosocial risk factors. Result Out of 1311 women recruited antenatally, 1240 (356 with and 884 without antenatal depressive symptoms) were followed up in the postnatal period. Among 356 women with antenatal depressive symptoms, the elevated symptoms persisted into postnatal period in 138 women (38.8%). Out of 884 women without antenatal depressive symptoms, 136 (15.4%) experienced incident elevated depressive symptoms postnatally. The prevalence of high postnatal depressive symptoms in the follow-up sample was 274 (22.1%). Higher intimate partner violence scores in pregnancy were significantly associated with greater risk of incident depressive symptoms [adjusted Risk Ratio (aRR) = 1.06, 95% CI: 1.00, 1.12]. Each 1-point increment in baseline PHQ-9 score predicted an increased risk of incidence of postnatal depressive symptoms (aRR = 1.29, 95% CI: 1.15, 1.45). There was no association between self-reported pregnancy complications, medical conditions or experience of threatening life events with either incidence or persistence of depressive symptoms. Conclusion Psychological and social interventions to address intimate partner violence during pregnancy may be the most important priorities, able to address both incident and persistent depression.